Comparing English and Indonesian Abbreviation Systems: A Contrastive Linguistic Study - Tisya Amalia Putri Sitorus; Fitri Aisyah Amini Nst; Dea Nita Aulia; Dini Nur Aini; Nazwa Atalia Zahra; Siti Ismahani (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Abbreviation is a common linguistic strategy used to achieve efficiency and clarity in modern communication. This study examines the abbreviation systems of English and Indonesian through a contrastive linguistic approach, focusing on morphological patterns, phonological constraints, and usage conventions. Employing a qualitative descriptive design, the data were collected from established linguistic references and analyzed using classical contrastive analysis principles. The findings reveal that English abbreviation formation is structurally flexible, allowing both pronounceable acronyms and non-pronounceable initialisms, often maintaining complex consonant clusters and orthographic capitalization. In contrast, Indonesian abbreviation formation is strongly influenced by phonological preferences, particularly ease of pronunciation and conformity to open syllable structures, resulting in forms that closely resemble ordinary lexical items. These structural differences suggest potential sources of negative transfer for language learners and challenges in translation practices. The study concludes that abbreviation systems are shaped not only by linguistic rules but also by sociocultural and communicative needs. Understanding these contrasts is essential for language teaching, translation, and further comparative linguistic research.